Perlindungan Aset Lokal Yang Belum Terdaftar Indikasi Geografis Dari Kejahatan Cybersquatting - Dewi, Ni Komang Cempaka; Cakabawa Landra, Putu Tuni (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020), 2020)
Many local Indonesian assets have not been protected by Geographical Indications and very vulnerable to being exploited by irresponsible parties, one of which is cybersquatting crime by registering a website address on the internet using the name of a geographically indicated product without the right as the legal owner then selling the domain name for expensive price causing losses for local Indonesian assets that have not been registered with Geographical Indications. The problem of this research: How is the legal protection on local assets that have not yet registered as Geogragraphical Indication from cybersquatting crime. The purpose of this research is to find out the legal protection of unregistered local asset as geographical indication product from cybersquatting. The legal research method used is the normative legal research method using the statutory approach and the conceptual approach. The result of the research is the protection of local assets from cybersquatting crimes that have not been protected by Geographical Indications is protected under Article 23 of the ITE Law and for every person whose rights are violated due to cybersquatting crimes, they have the right to file a lawsuit to cancel the unauthorized use of domain names by other parties.